2020
DOI: 10.1016/j.ceca.2020.102256
|View full text |Cite
|
Sign up to set email alerts
|

Divalent cations permeation in a Ca2+ non-conducting skeletal muscle dihydropyridine receptor mouse model

Abstract: The dihydropyridine receptor has a function of voltage-gated Ca 2+ channel in muscle • The N617D mutation in the α1 subunit confers non-Ca 2+ conductivity to the channel • Ba 2+ and Mn 2+ ions are found to permeate the mutant channel • External Ca 2+ strongly blocks Ba 2+ currents through the mutant channel • N617D mutation located outside the selectivity filter influences channel permeation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Prior to trituration, the bottom of the experimental chamber was covered with a thin layer of silicone grease. This enabled single fibers from zebrafish or mouse to be covered with additional silicone, so that a 50–100-μm-long portion of the fiber extremity was left out, as previously described ( Idoux et al, 2020 ). The culture medium solution was replaced by the extracellular solutions (see Solutions).…”
Section: Methodsmentioning
confidence: 99%
“…Prior to trituration, the bottom of the experimental chamber was covered with a thin layer of silicone grease. This enabled single fibers from zebrafish or mouse to be covered with additional silicone, so that a 50–100-μm-long portion of the fiber extremity was left out, as previously described ( Idoux et al, 2020 ). The culture medium solution was replaced by the extracellular solutions (see Solutions).…”
Section: Methodsmentioning
confidence: 99%
“…Single fibers were isolated by a 50-minute enzymatic treatment at 37° C using a Tyrode solution containing 2 mg/mL collagenase type I (Sigma). Fibers were voltage-clamped using the silicone clamp technique as previously described [ 47 ]. Briefly, a major part of a single fiber was electrically insulated with silicone grease and a micropipette was inserted into the fiber through the silicone layer to voltage clamp the portion of the fiber free of grease (50 to 150 μm length) using a patch-clamp amplifier (Bio-Logic RK-400, Claix, France) in whole-cell configuration.…”
Section: Methodsmentioning
confidence: 99%
“…Single fibers were isolated by a 50-minute enzymatic treatment at 37° C using a Tyrode solution containing 2 mg/mL collagenase type I (Sigma). Fibers were voltage-clamped using the silicone clamp technique as previously described (47).…”
Section: Myofiber Isolation and Electrophysiologymentioning
confidence: 99%
“…Unlike the N617D mutation, another nonconductive mutation, E1014K [ 9 , 10 ], disrupting the quadruple aspartate motif, contrasts with the report by Idoux et al [ 32 ]. The E1014K mutation on Ca V 1.1 showed enhanced muscle fatigue, altered muscle composition, and metabolic issues in an engineered mouse [ 9 , 10 ].…”
Section: Ca V 11 Is An L-type Ca 2+ ...mentioning
confidence: 98%
“…The authors found no significant differences in muscle performance or excitability when comparing N617D mice with the wild-type counterpart. Using dissociated FDB fibers from these mice, Idoux and colleagues [ 32 ] observed later that N617D conducted Mn 2+ and Ba 2+ in the absence of extracellular Ca 2+ . The Ba 2+ conductance was potently blocked by Ca 2+ , indicating a higher selectivity for Ca 2+ over Ba 2+ .…”
Section: Ca V 11 Is An L-type Ca 2+ ...mentioning
confidence: 99%